Development of targeted therapy in uterine serous carcinoma, a biologically aggressive variant of endometrial cancer. Issue 1 (January 2012) - El-Sahwi, Karim S; Schwartz, Peter E; Santin, Alessandro D
Endometrial cancer (EC) is the most common female genital malignancy in the USA. Most carcinomas arising from the uterus are estrogen dependent and are associated with obesity and hypertension. They are designated type I ECs and typically, due to their early diagnosis secondary to postmenopausal bleeding, have a good prognosis. By contrast, type II ECs develop in older patients, are not hormone dependent and are responsible for most recurrences and deaths from EC. Uterine serous cancer constitutes up to 10% of all endometrial tumors, and represents the most biologically aggressive variant of type II EC. This article will describe the most salient molecular markers that have been identified in uterine serous cancer, thus far with emphasis on the use of erbB2 (HER2/neu) as the first of a series of therapeutic markers for the treatment of this highly-aggressive subset of ECs.